Hubungan Religiusitas dan Bersyukur dengan Kesejahteraan Psikologis pada Siswa SMA Methodist 7 Medan - Masniari Eva Juniar Panjaitan; Hasanuddin Hasanuddin; Sri Milfayetty (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2022)
Psychological well-being is a happy state that can be seen from the individual having a purpose in life. The focus of this research is to look at the psychological well-being of students at SMA Methodist 7 Medan which is then associated with religiosity and gratitude. The purpose of this study was to determine the relationship between religiosity and gratitude with psychological well-being in students of SMA Methodist 7 Medan. Participants in this research amounted to 180 students using total sampling technique. This type of research is a quantitative study, where data collection uses a scale which will later be processed with SPSS rocks.The results showed that there was a significant positive relationship between religiosity and psychological well-being seen from the coefficient value (Rxy) = 0.613 with p = 0.000 0.050, then there is a significant positive relationship between gratitude with psychological well-being seen from the value of the coefficient (Rxy) = 0.828 with p = 0.000 0.050, and there is a significant positive relationship between religiosity and gratitude. with psychological well-being by using regression analysis method, it is known that the coefficient value (Rxy) = 0.845 with p = 0.000 0.050. So it can be concluded that there is a significant relationship between religiosity and gratitude with psychological well-being in students of SMA Methodist 7 Medan.